The Film History in Terms of Popularity. An Interview with John Sedgwick - Szczepanik, Petr (Iluminace, 2006)
An interview with the leading American film theorist, historian and columnist John Sedgwick about his research and publishing.
Keywords: film historians; film theorists; film scholars; film science and research